APLIKASI SOFTWARE GEOSTUDIO 2007 SLOPE/WUNTUK ANALISIS KESTABILAN LERENG DI TAMBANG MUARA TIGA BESAR UTARA PT BUKIT ASAM (PERSERO) Tbk SUMATERA SELATAN: The Application of Software Geostudio 2007 Slope/w to analysis slope instability in Mine Muara Tiga Besar Utara at PT Bukit Asam (Persero)Tbk South Sumatera - Putra, Irza Tri; Guskarnali, Guskarnali; Irvani, Irvani (MINERAL, 2017)
PT Bukit Asam (Persero) Tbk is one of the State Owned Enterprises engaged in coal mining. Presente of Mine Muara slopes at Muara Tiga Besar Utara would be harmful to workers and the mechanical vehicle, because the soil/ rock is likely to experience landslides or falling. This study was conducted to determine the value of slope safety factor RKAP 2017 and redesign the slopes with a safe condition. The data used in this study include the value of cohesion (c’) the angle of friction (ϕ’) and density (γ). Retrieval of research data obtained from the test results did not drainage unconsolidated triaxial (UU) and test weight of soil/rock with Paraffin Wax Method, and then did the processing of data by using Software Geostudio 2007 Slope/w to determine the value of the safety factor of the slope. Factors affecting slope instability in Mine Muara Tiga Besar Utara were the geometry of the slope, weather/climate, vibration, and physical properties and mechanics of soil/rock composed of the density (γ), ie 1.203 to 2.025 gr/cm3, the value of cohesion (c’), which is 34 to 266 kPa and the shear angle value (ϕ’), ie 17.65 to 35.210. The results of slope stability analysis indicate that the value of slope safety factor RKAP 2017 was below 1.25, so the potential occurrence of landslides, while the redesign slope slope with the security condition had a value of safety factor is above 1.25, so that no potential landslides.